PENTINGNYA BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA - Dewi Kurniawati; Arta Ekayanti (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study has aims to describe the importance of critical thinking skills in mathematics learning. This study uses descriptive qualitative methods using knowledge or facts about the importance of necessary thinking skills in learning mathematics. This study using content analysis techniques that are an in-depth discussion of the contents of the journal associated with critical thinking skills on mathematics learning. Learning mathematics is basic science, so it is crucial in the learning process. In education, mathematics requires necessary thinking skills. Critical thinking can be trained and developed through the process of learning mathematics, while mathematics material is understood through critical thinking. Critical thinking skills are interconnected and continuous. So necessary thinking skills are essential in learning mathematics.